The effect of using aids manufactured to perform the maximum speed of the hands in learning the skill of hitting baseball for ages (under 12 years) - nbraz, younis; Lazim, Ali (Journal of Physical Education, 2023)
The aim of the research is to find out the effect of using manufactured auxiliary tools to perform the maximum speed of the hands in learning the skill of hitting baseball (Baseball) for ages under 12 years. The research problem was identified through the researcher’s practice of baseball as a player in the national team. Especially at the beginning of learning, and the research hypothesized that the use of manufactured auxiliary tools has a positive effect to perform the maximum speed of the hands in learning the skill of hitting with baseball. (20) beginner players with ages under (12) years, and the research sample consisted of (12) players, and two players were excluded for their participation in the exploratory experiment. Manufactured aids in teaching the skill of hitting baseball and moving away from the traditional method